Cognitive abilities, brain white matter hyperintensity volume, and structural network connectivity in older age. Issue 2 (14th November 2017) - Wiseman, Stewart J.; Booth, Tom; Ritchie, Stuart J.; Cox, Simon R.; Muñoz Maniega, Susana; Valdés Hernández, Maria del C.; Dickie, David Alexander; Royle, Natalie A.; Starr, John M.; Deary, Ian J.; Wardlaw, Joanna M.; Bastin, Mark E.
Abstract: Objective: To assess brain structural connectivity in relation to cognitive abilities in healthy ageing, and the mediating effects of white matter hyper‐intensity (WMH) volume. Methods: MRI data were analysed in 558 members of the Lothian Birth Cohort 1936. Brains were segmented into 85 regions and combined with tractography to generate structural connectomes. WMH volume was quantified. Relationships between whole‐brain connectivity, assessed using graph theory metrics, and four major domains of cognitive ability (visuospatial reasoning, verbal memory, information processing speed and crystallized ability) were investigated, as was the mediating effects of WMH volume on these relationships. Results: Visuospatial reasoning was associated with network strength, mean shortest path length, and global efficiency. Memory was not associated with any network connectivity metric. Information processing speed and crystallized ability were associated with all network measures. Some relationships were lost when adjusted for mean network FA. WMH volume mediated 11%–15% of the relationships between most network measures and information processing speed, even after adjusting for mean network FA. Conclusion: Brain structural connectivity relates to visuospatial reasoning, information processing speed and crystallized ability, but not memory, in this relatively healthy age‐homogeneous cohort of 73 year olds. When adjusted for mean FA across the network, most relationships are lost, except with information processing speed suggesting that the underlying topological network structure is related to this cognitive domain. Moreover, the connectome‐processing speed relationship is partly mediated by WMH volume in this cohort. Hum Brain Mapp 39:622–632, 2018 . © 2017 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.